2016
DOI: 10.1007/s13205-016-0546-z
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of bacteria and archaea in the rhizosphere of bioenergy crop Jatropha curcas

Abstract: Plant-microbial interaction in rhizosphere plays vital role in shaping plant’s growth and ecosystem function. Most of the rhizospheric microbial diversity studies are restricted to bacteria. In natural ecosystem, archaea also constitutes a major component of the microbial population. However, their diversity is less known compared to bacteria. Experiments were carried out to examine diversity of bacteria and archaea in the rhizosphere of bioenergy crop Jatropha curcas (J. curcas). Samples were collected from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 46 publications
2
7
0
Order By: Relevance
“…Microbial diversity was highest in the Middle Gangetic Plain region as compared with another geographical region. Similar results have been observed with microbial diversity of rhizospheric Jatropha crop, which showed to be highest in Noida and Bhopal regions rather than Jabalpur in India [ 79 ]. Similar results were observed in Ranunculus glacialis rhizospheric microbial diversity [ 80 ].…”
Section: Discussionsupporting
confidence: 82%
“…Microbial diversity was highest in the Middle Gangetic Plain region as compared with another geographical region. Similar results have been observed with microbial diversity of rhizospheric Jatropha crop, which showed to be highest in Noida and Bhopal regions rather than Jabalpur in India [ 79 ]. Similar results were observed in Ranunculus glacialis rhizospheric microbial diversity [ 80 ].…”
Section: Discussionsupporting
confidence: 82%
“…Although endophytes are prevalent, the literature about this group of microorganisms from renewable energy plants J. curcas is scarce. Some studies of the endophytic and rhizospheric bacteria diversity associated with J. curcas found the phyla Actinobacteria, Acidobacteria, Chlroflexi, Firmicutes, and Verrucomicrobia Annapurna;Saraf, 2012;Dubey et al 2016;Madhaiyan et al, 2012;Qin et al, 2015); which demonstrates the ability of the phyla found in the present study in Annapurna;Saraf, 2012;Madhaiyan et al, 2012;Madhaiyan et al, 2013). These genera have already been described as capable of promoting plant growth in various other crops (Chauhan, Bagyaraj, Sharma, 2013;Castro et al, 2017;Batista et al, 2018).…”
Section: Discussionsupporting
confidence: 74%
“… Archaea Discovery location Potential function Reference Crenarchaeota Mycorrhizospheres scots pine [10] Rhizosphere of macrophyte Littorella uniflora Ammonia oxidation [24] Marine or wetland Sulfur reduction ( dissimilatory sulfite reductases ) [37] Sulfolobus acidocaldarius Indole acetic acid production [41] Rhizosphere of Jatropha curcas Nitrification [48] Thermoproteaceae, Sulfolobaceae Desulfurococcaceae Bacteriosin or terpene in genome [50] Euryarchaeota Methanogens , Rice cluster Ⅰ Rice fields Methane-oxidizing archaea [3] , [32] , [59] Marine or wetland Sulfur reduction ( dissimilatory sulfite reductases ) [37] Forest and grassland soil Phosphatase enzymes phoD and phoX [26] Halobacteria Rhizophora mangle Phosphorous solubilization [27] , [28] Halobactierum Halococcus Halonemum strobilaceum (Chenopodiaceae) Phosphorous Solubilization [27] , [29] Halolamina Rhizosphere of grasses in hypersaline soil Phosphorous solubilization [27] , [30] Methanomicrobia, Halobacteriaceae Rhizosphere of Bog vagetation CO2 fixation, oxidative stress …”
Section: Introductionmentioning
confidence: 99%
“…Plants can also grow in environments with high levels of abiotic stress. Metagenomic analysis of the rhizosphere of Jatropha curcas, which adapted to grow under salt stress and high temperature conditions, showed high abundances of Crenarchaeota and Euryarchaeota [48] ( Table 1 ). Although the detailed reason is not known, Crenarchaeota and Euryarchaeota may help the Jatropha curcas adapt to salt stress and high temperature condition.…”
Section: Introductionmentioning
confidence: 99%